Understanding "watchers" on GitHub - Sheoran, Jyoti; Blincoe, Kelly; Kalliamvakou, Eirini; Damian, Daniela; Ell, Jordan (2014 Mining Software Repositories, 2014)
Users on GitHub can watch repositories to receive notifications about project activity. This introduces a new type of passive project membership. In this paper, we investigate the behavior of watchers and their contribution to the projects they watch. We find that a subset of project watchers begin contributing to the project and those contributors account for a significant percentage of contributors on the project. As contributors, watchers are more confident and contribute over a longer period of time in a more varied way than other contributors. This is likely attributable to the knowledge gained through project notifications.